Influence of functionalized hematite nanoparticles as a reinforcer for composite PVDF‑PEG membrane for BPF rejection: permeability and anti‑fouling studies - Katibi, Kamil Kayode; Md Yunos, Khairul Faezah; Che Man, Hasfalina; Aris, Ahmad Zaharin; Nor, Mohd Zuhair Mohd; Azis, Rabaah Syahidah (Springer, 2022)
Pollution of water resources is a high-priority global issue. Nanocomposite membrane technology is an advanced purification technology that offers superior separation and filtration of organic and inorganic contaminants from water along with prolonged life of the membrane. In this study, iron oxide (Fe2O3) nanoparticles (NPs) were synthesized using the facile sol–gel technique, modified by 3-Aminopropyl tri-ethoxy silane (APTES), and analyzed to identify the structural properties, functional groups, elemental constituents of the NPs, and the surface modification of Fe2O3 NPs by APTES. FTIR, EDX, and XRD analyses demonstrated that Fe2O3 NPs were successfully modified. Then, pristine polyvinylidene Fluoride (PVDF)- Polyethylene glycol (PEG) based membrane and composite membrane blended with modified Fe2O3 NPs were fabricated via non-solvent induced phase inversion (NIPs) technique. The resultant fabricated membranes were analyzed by the contact angle, FESEM, EDX, surface zeta-potential, porosity, flux, resistance to fouling, and bisphenol F (BPF) rejection. The flux, resistance to fouling, and BPF rejection were enhanced with the functionalized Fe2O3 NPs loading increment. Also, the membrane blended with 1.5 wt of modified Fe2O3 NPs displayed a remarkable performance with fluxes of 125.47 L/m2 h and 117.31 L/m2 h, least contact angle of 58.5° and superior BPF rejection (90.69) compared to other membranes. The results of anti-fouling tests indicated a superior flux recovery ratio (FRR) and relative flux reduction (RFR) of 78.83 and 14.05 for membrane with 1.5 wt Fe2O3 NPs following three cycles of filtration for a complete 5 h which is considerably higher than other membranes.